2014
DOI: 10.1007/s00277-014-2154-5
|View full text |Cite|
|
Sign up to set email alerts
|

Response to hydroxycarbamide in pediatric β-thalassemia intermedia: 8 years’ follow-up in Egypt

Abstract: Hydroxycarbamide (hydroxyurea or HU) has been shown to increase fetal hemoglobin (HbF) in patients with β-thalassemia intermedia (TI). The reported effects of HU in increasing the total hemoglobin (Hb) have been inconsistent. Studies of long-term therapy with HU in pediatric TI are rather uncommon. A retrospective observational study was carried out to evaluate the clinical responses to HU in Egyptian patients with β-TI. One hundred patients; children (n = 82, mean age 9.9 ± 4.1 years) and adults (n = 18) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…No correlation could be established with respect to age, sex, or genotype toward the prediction of response to hydroxyurea therapy. [27] Our study also showed a reduction in serum ferritin levels in both the groups after hydroxyurea therapy. This is in agreement with our earlier report where hydroxyurea has been shown to be a potential iron chelator in an animal model and transfusion-dependent β-thalassemia patients.…”
Section: Discussionsupporting
confidence: 72%
“…No correlation could be established with respect to age, sex, or genotype toward the prediction of response to hydroxyurea therapy. [27] Our study also showed a reduction in serum ferritin levels in both the groups after hydroxyurea therapy. This is in agreement with our earlier report where hydroxyurea has been shown to be a potential iron chelator in an animal model and transfusion-dependent β-thalassemia patients.…”
Section: Discussionsupporting
confidence: 72%
“…39,41,42 Many patients, particularly in the ATG-BuCy group, were treated with Hu in order to minimize both liver and spleen size as well as extramedullary hematopoiesis. 43,44 There is a general perception that BMT centers need complex engineering standards requiring undue investments, even more so in developing countries, where the risk of infection might be greater. In fact, there is no evidence that the latter is true.…”
Section: Discussionmentioning
confidence: 99%
“…For patients with TDT, the groups were defined by the following parameters: MaR, removal from the blood transfusion, MiR, ≥50% reduction in transfusion requirement, and NR, <50% reduction in transfusion requirement. 4,7 Statistical analysis. SPSS Statistics 21.0 (SPSS Inc., Chicago, IL, USA) was applied for data analysis.…”
Section: Standard For Determination Of Efficacy For Patientsmentioning
confidence: 99%
“…Hydroxyurea, approved by the FDA for the treatment of sickle cell disease (SCD), is also the most widely used HbF inducer in β-thalassemia. However, the clinical application of hydroxyurea is limited by the low number of significant responders, 7,8 reduced clinical response with long follow-up, 9,10 and bone marrow suppression. 11 Therefore, better treatments facilitating improved outcomes are increasingly important.…”
mentioning
confidence: 99%